2004
DOI: 10.1144/gsl.sp.2004.229.01.17
|View full text |Cite
|
Sign up to set email alerts
|

Phreatomagmatic eruptions on the Ontong Java Plateau: chemical and isotopic relationship to Ontong Java Plateau basalts

Abstract: Abstract:The compositions of glass clasts in volcaniclastic rocks recovered from drilling at Site 1184 on the eastern salient of the Ontong Java Plateau (OJP) are investigated using microbeam analytical methods for major, minor and trace elements. These data are compared with whole-rock elemental and isotopic data for bulk tuff samples, and with data from basalts on the high plateau of the OJP. Three subunits of Hole 1184A contain blocky glass clasts, thought to represent the juvenile magmatic component of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…As noted earlier, the Pb-isotopic signature appears to have been affected by alteration. White et al (2004) observed that, in the bulk volcaniclastic rocks at Site 1184, Sr-and Pbisotope ratios have been affected by sea-water alteration. The same type of result was also seen in the Singgalo-type vitric tuff at Site 1183 (Tejada et al 2004).…”
Section: The Influence Of Alterationmentioning
confidence: 97%
See 2 more Smart Citations
“…As noted earlier, the Pb-isotopic signature appears to have been affected by alteration. White et al (2004) observed that, in the bulk volcaniclastic rocks at Site 1184, Sr-and Pbisotope ratios have been affected by sea-water alteration. The same type of result was also seen in the Singgalo-type vitric tuff at Site 1183 (Tejada et al 2004).…”
Section: The Influence Of Alterationmentioning
confidence: 97%
“…However, as indicated in Figure 4b, alteration has variably increased Na20 and K20 levels. Fresh glass clasts analysed by White et al (2004) plot as low-K tholeiites. When elements considered to be immobile under low-temperature alteration conditions are used to discriminate between alkali and tholeiitic basalts, the basalt clasts plot strictly in the tholeiitic field ( Fig.…”
Section: Major Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Basaltic units in the upper part of the Nauru Basin succession drilled at Site 462 were originally described as sills (Larson et al 1981), but Saunders (1986) has argued that these are thick sheet flows. The only evidence for subaerial or shallow-water volcanism during emplacement of the OJP is provided by the thick volcaniclastic succession at Site 1184 (Thordarson 2004;White et al 2004), two thin intervals of vitric tuff in the Aptian limestone immediately above basement at Site 1183 (Mahoney et al 2001) and a vitric tuff just above basement at Site 289. There is no evidence for subaerial eruption of lava flows, and the CO2 contents of basaltic glass (Michael 1999;Roberge et al 2004) provide convincing evidence for relatively deep submarine eruption at all the drill sites on and around the OJP.…”
Section: Published 4~mentioning
confidence: 99%
“…In contrast, Thordarson (2004) interprets the MVDs as shower-bedded fall layers from 7-11 phreatomagmatic eruptions, perhaps comparable in style to the 1783 Laki eruption in Iceland (Thordarson andSelf, 1993, 2003). Several lines of evidence (paleomagnetism; major, trace element and isotope geochemistry; Ar-Ar dating of unaltered juvenile components) suggest that these MVDs are related to the main (Cretaceous) phase of Ontong Java volcanism (Chambers et al, 2004;Fitton and Godard, 2004;Riisager et al, 2004;White et al, 2004), despite the middle Eocene age of nannofossils (Shipboard Scientific Party, 2001). …”
Section: -Ontong Java Plateaumentioning
confidence: 99%